2006
DOI: 10.1111/j.1600-0579.2006.00395.x
|View full text |Cite
|
Sign up to set email alerts
|

Hand and nickel‐titanium root canal instrumentation performed by dental students: a micro‐computed tomographic study

Abstract: The aim of this study was to evaluate root canals instrumented by dental students using the modified double-flared technique, nickel-titanium (NiTi) rotary System GT files and NiTi rotary ProTaper files by micro-computed tomography (MCT). A total of 36 root canals from 18 mesial roots of mandibular molar teeth were prepared; 12 canals were prepared with the modified double-flared technique, using K-flexofiles and Gates-Glidden burs; 12 canals were prepared using System GT and 12 using ProTaper rotary files. Ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
2
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 20 publications
2
54
2
5
Order By: Relevance
“…Regarding the time spent for preparation, as expected, rotary instrumentation was faster than manual, and the difference was statistically significant. Other studies also reported a higher speed with rotary instrumentation when performed by inexperienced students 7,14,19,22) . This greater speed is due to the difference in design of these two types of instrumentation.…”
Section: Discussionmentioning
confidence: 91%
“…Regarding the time spent for preparation, as expected, rotary instrumentation was faster than manual, and the difference was statistically significant. Other studies also reported a higher speed with rotary instrumentation when performed by inexperienced students 7,14,19,22) . This greater speed is due to the difference in design of these two types of instrumentation.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies suggested that undergraduate dental students can successfully prepare molar root canals with rotary instrument, and these instruments are increasingly being integrated into clinical courses (4,12,16,(24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…In two earlier studies on NiTi rotaries, inexperienced dental students were able to prepare simulated root canals with Flexmaster (5) and mesial root canals in lower molars with ProTaper and GT (16) rotary files with lower risk of procedural errors and faster than with hand instruments.…”
Section: Introductionmentioning
confidence: 99%
“…According to the results of these researchers, it was believed that variations in canal geometry before preparation have more influence on the changes during preparation than the techniques and instruments themselves , as nearly all instrumentation techniques left 35% or more of the canals' surface area unchanged. Furthermore different instrument types demonstrated few differences on the general effect of preparation ), but caused effects at different parts of the same root canal (Bergmans et al, 2003;Peters et al, 2003;Ozgur Uyanik et al, 2006;Peru et al, 2006). The majority of instruments enable easy access and can be manipulated safely with respect to different experience levels of users.…”
Section: Evaluation Of Root Canal Preparationmentioning
confidence: 99%
“…However, with the Micro-CT systems, the 3D evaluation of canal preparation has been made easy and convenient (Bergmans et al, 2001). A number of researchers have evaluated and compared different root canal instruments with Micro-CT, including K-files , K-flexofiles (Peru et al, 2006), Profile (Bergmans et al, 2001;Cheung and Cheung, 2008;Versiani et al, 2008), Protaper (Bergmans et al, 2003;Ozgur Uyanik et al, 2006;Peru et al, 2006;Versiani et al, 2008), Hero Shaper (Ozgur Uyanik et al, 2006;Cheung and Cheung, 2008), System GT Peru et al, 2006;Versiani et al, 2008), Lightspeed , K3 (Bergmans et al, 2003), Endo-Eze AET (Paque et al, 2005), RaCe (Ozgur Uyanik et al, 2006), and Flexmaster (Hubscher et al, 2003). With the data from such scans, it is possible to measure many changes before and after preparation, such as surface area and volume of root canal, amount of dentin volume removed, canal "thickness" (diameter), prepared surface, curvature, canal transportation, structure model index (SMI), transportation of centers of mass, canal straightening proportion of unchanged, canal centering ratio Peters et al, 2003).…”
Section: Evaluation Of Root Canal Preparationmentioning
confidence: 99%